Development and characterization of mixed bovine and goat milk cream: Physical-chemical, microgical and sensorial (Research, Society and Development, 2024)
Goat milk derivatives are foods with high added value, having characteristic aroma and flavor attributes. Considering the numerous goat herd in the Northeast and the need to value this milk and its derivatives, this study aimed to prepare three creamy mixed butters of bovine and goat milk cream in different proportions, characterizing them in terms of microbiological, physicochemical aspects. and sensory. Analyzes were performed to count total coliforms, thermotolerant coliforms, coagulase positive Staphylococcus, total mesophilic aerobic plaque count and Salmonella detection. For the physicochemical characterization, analyzes of titratable acidity in lactic acid, moisture, ash, lipids by Gerber and sodium chloride were performed. Sensory tests of acceptability, purchase intent and check-all-that-apply (CATA) were performed. In the physical-chemical evaluation there was a significant variation in ash, moisture and sodium chloride. In the microbiological analysis, the three butter samples evaluated are in accordance with Brazilian legislation. The acceptance and purchase intent sensory tests proved that, in general, all samples were well accepted by the tasters and with good purchase intent. The CATA test pointed out the characteristics of each sample, with A1 being the firmer and saltier, A2 the softest and A3 with more goat flavor and whiter.